To solve the system from part (a), we'll use the method of substitution.
First, let's solve equation (C) for y:
5x + 3y = 60
3y = 60 - 5x
y = (60 - 5x)/3
Now substitute this expression for y into equation (A):
10x + 3y = 90
10x + 3((60 - 5x)/3) = 90
10x + 60 - 5x = 90
5x + 60 = 90
5x = 30
x = 30/5
x = 6
Now substitute the value of x into equation (C) to find y:
5x + 3y = 60
5(6) + 3y = 60
30 + 3y = 60
3y = 60 - 30
3y = 30
y = 30/3
y = 10
Therefore, the solution to the system of equations is (x, y) = (6, 10).
10x + 3y = 90
C.
5x + 3y = 60
b) Solve the system from part (a).
(Type an ordered pair.)
1 answer